2020
DOI: 10.1016/j.heliyon.2019.e02957
|View full text |Cite
|
Sign up to set email alerts
|

Biometry, condition factors and length-weight relationships of sixteen fish species in Iwopin fresh-water ecotype of Lekki Lagoon, Ogun State, Southwest Nigeria

Abstract: Study on biometry, length-weight relationships and condition factors of 139 fishes covering 11 families and 16 species inhabiting Iwopin fresh water ecotype of Lekki Lagoon, were provided. The fish species were obtained from the major landing sites of Iwopin from July to September, 2017. As a result, Chrysichthys nigrodigitatus was the most abundant while Polypterus senegalus, Sphyraena barracuda and Dagetichthys lakdoensis constituted the least groups of populations. The Fulton condition factor (K) values sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…The range of condition from the data analysis factor is 1.89-2.28 (Tabel 2), whereas if more > 2 then dominated by fish with maturity level of gonad (Esmaeili et al 2017;Masoomizadeh et al 2018;Famoofo and Abdul 2020) while weight value observed in each species per station is low and high compared to the predicted weight. This value indicates that there are areas of poor water conditions to support growth, but the value of the condition factor gives an average value above 100.…”
Section: Discussionmentioning
confidence: 95%
“…The range of condition from the data analysis factor is 1.89-2.28 (Tabel 2), whereas if more > 2 then dominated by fish with maturity level of gonad (Esmaeili et al 2017;Masoomizadeh et al 2018;Famoofo and Abdul 2020) while weight value observed in each species per station is low and high compared to the predicted weight. This value indicates that there are areas of poor water conditions to support growth, but the value of the condition factor gives an average value above 100.…”
Section: Discussionmentioning
confidence: 95%
“…Inland fisheries including Nigeria for decades has been a driving force of economies of most countries of the world contributing to the country's GDP 16 . Inland fisheries are rooted in socially and culturally complex societies 17 ; they play a vital role in the livelihood of people in many parts of the developed and developing world 11,17 including Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…
The fish composition of the three study sites of the reservoir were studied over a period of fifteen months (January, 2020 -March, 2021. A total of twenty-eight (28) fish species emanating from fourteen ( 14) families were obtained.
…”
mentioning
confidence: 99%
“…The length-weight relationship (LWR) has significant applications in regard to fisheries management and fish biology. The relationship facilitates the growth studies, calculation of condition indices, estimation of length from known weight, estimation of weight at age, evaluation of life-history traits, and comparisons of the morphological characters between and among the populations inhabiting a variety of habitats and/or region (Abdul & Famoofo, 2020;Alam et al, 2019;Froese, 2006;Froese et al, 2011;Goncalves et al, 1997). It is also fundamental to population dynamics studies and for assessment of fish stocks (Binohlan & Pauly, 1998;Froese, 2006;Petrakis & Stergiou, 1995).…”
Section: Introductionmentioning
confidence: 99%